Hepatocellular Carcinoma Demonstrates Heterogeneous Growth Patterns in a Multicenter Cohort of Patients With Cirrhosis. Issue 5 (25th October 2020) - Rich, Nicole E.; John, Binu V.; Parikh, Neehar D.; Rowe, Ian; Mehta, Neil; Khatri, Gaurav; Thomas, Smitha M.; Anis, Munazza; Mendiratta‐Lala, Mishal; Hernandez, Christopher; Odewole, Mobolaji; Sundaram, Latha T.; et al.
Abstract : Background and Aims: There are limited data on hepatocellular carcinoma (HCC) growth patterns, particularly in Western cohorts, despite implications for surveillance, prognosis, and treatment. Our study's aim was to quantify tumor doubling time (TDT) and identify correlates associated with indolent and rapid growth. Approach and Results: We performed a retrospective multicenter cohort study of patients with cirrhosis diagnosed with HCC from 2008 to 2017 at six US and European health systems with two or more contrast‐enhanced imaging studies performed ≥ 30 days apart prior to HCC treatment. Radiologists independently measured tumors in three dimensions to calculate TDT and specific growth rate (SGR). We used multivariable ordinal logistic regression to identify factors associated with indolent (TDT > 365 days) and rapid (TDT < 90 days) tumor growth. In the primary cohort (n = 242 patients from four centers), median TDT was 229 days (interquartile range [IQR], 89‐627) and median SGR was 0.3% per day (IQR, 0.1%‐0.8%). Over one‐third (38%) of HCCs had indolent growth, 36.8% intermediate growth, and 25.2% rapid growth. In multivariable analysis, indolent growth was associated with larger tumor diameter (odds ratio [OR], 1.15, 95% confidence interval [CI], 1.03–1.30) and alpha‐fetoprotein < 20 ng/mL (OR, 1.90; 95% CI, 1.12‐3.21). Indolent growth was more common in nonviral than viral cirrhosis (50.9% versus 32.1%), particularly in patients with T1 HCC (OR, 3.41; 95% CI, 1.08‐10.80). Median TDT (169 days; IQR 74‐408 days) and SGR (0.4% per day) were similar in an independent cohort (n = 176 patients from two centers). Conclusions: In a large Western cohort of patients with HCC, we found heterogeneous tumor growth patterns, with one‐fourth exhibiting rapid growth and over one‐third having indolent growth. Better understanding different tumor growth patterns may facilitate a precision approach to prognostication and treatment.